1990
DOI: 10.3109/10826089009053173
|View full text |Cite
|
Sign up to set email alerts
|

Religious Values and Beliefs and Place of Residence as Predictors of Alcohol Use Among Chinese College Students in Singapore

Abstract: Data drawn from a detailed study of alcohol use among Chinese undergraduate college students in Singapore (N = 767) show identification with religious values and beliefs not to be a significant factor in terms of students' alcohol use. Students' place of residence (i.e., on campus in a hostel or off campus) was found to predict alcohol use but in a way opposite to the pattern commonly predicted - that is, students on campus tend to drink less than their off-campus counterparts. When religious values and belief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Koopmans, Slutske, Baal, and Boomsma (1999) found similar results among Dutch adolescents. Isralowitz and Ong (1990), studying Chinese undergraduate college students in Singapore, reported that religious values were not a significant factor in students' alcohol use. Miller (1998) concluded that religious involvement may be an important "protective factor" against alcohol misuse.…”
Section: Religion and Alcohol Usementioning
confidence: 99%
“…Koopmans, Slutske, Baal, and Boomsma (1999) found similar results among Dutch adolescents. Isralowitz and Ong (1990), studying Chinese undergraduate college students in Singapore, reported that religious values were not a significant factor in students' alcohol use. Miller (1998) concluded that religious involvement may be an important "protective factor" against alcohol misuse.…”
Section: Religion and Alcohol Usementioning
confidence: 99%
“…Most part of the studies has predominantly investigated the religious affiliation and the attendance to cults. However, several researchers 9,17,22,33 have also included variables such as: importance given to religiousness in life, religious commitment, measures of religiousness (belief in God, intensity of the faith, etc. ), personal religious practices (solitary prays, religious readings, etc.…”
Section: Variables Of Religiousnessmentioning
confidence: 99%
“…Although criminological research on religiosity in East Asia is extremely rare, 1 one existing study supports our supposition for a null finding. Isralowitz and Ong (1990) examined the association between religious values and beliefs and alcohol consumption among Chinese undergraduate students in Singapore ( N = 767), only to fail to find a significant association. Moreover, although research on Buddhism in Thailand has found significant negative associations between religiosity and substance use and sexual behavior among Thai adolescents (e.g., Chamratrithirong et al, 2010, 2013), Thailand is a predominantly Buddhist country (94.6% of the population), which differs from other East Asian countries that are religiously pluralistic.…”
Section: Religious Context In South Koreamentioning
confidence: 99%
“…Given this drastically different religious climate, it remains an important empirical question whether the research findings on religiosity garnered from Western samples can be generalizable to East Asia. Cognizant of this limitation of the extant literature, scholars have argued for further studies beyond Judeo-Christian Western boundaries (Helms et al, 2015; Isralowitz & Ong, 1990; Pickering & Vazsonyi, 2010; Pitel et al, 2012). Given this backdrop and pursuant to the advice of earlier scholars, we examine the association between religiosity and adolescents’ involvement in deviant behaviors in South Korea, an East Asian country epitomized by religious pluralism and a large population of atheists.…”
Section: Introductionmentioning
confidence: 99%